PENGARUH DEFLEKTOR DAN DIFFUSOR TERHADAP PERFORMA TURBIN ANGIN SUMBU VERTIKAL DARRIEUS H BLADE DENGAN AIRFOIL NACA 5317 - Nurmand Bernard Adrianto; Erdiansyah, Erdiansyah; Alika Putra Demi Laksa (Bajang Institute, 2024)
This study analyzes the effect of using a deflector and diffuser on the performance of a vertical axis wind turbine (VAWT) Darrieus H-Blade with NACA 5317 airfoil. The deflector is a flat plate (600 mm x 600 mm), and the diffuser is a semicircle (575.2 mm in diameter), tested with wind speeds varying from 3–5 m/s and a blade pitch angle of 50°. The tests involve SolidWorks simulation and direct testing, focusing on torque, power, power coefficient, rotational speed, and efficiency. Results show that adding the deflector and diffuser increases torque from 1.456 N.m to 1.92 N.m and efficiency from 49.27% to 88.07% at a wind speed of 5 m/s. This combination also extends the optimal TSR range and enhances power output.